KONSEP DASAR PENGAJARAN BAHASA ARAB - Fatmawati Fatmawati (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2017)
AbstractIn every learning process, there is always a concept or planning that has been planned by the teacher, because the concept is a guide to move forward to get results which appropriate with what we expect. In the Arabic Language teaching process, the basic concept is the initial idea / planning that has been prepared to teach the Arabic language in accordance with the activity or teaching process between the educators and the learners. The teacher is the main role in Arabic Language teaching process. But it does not mean that it only depend on active teachers , while the learners are accepted to be passive in this teaching process. Teaching requires the activeness of both parties who are both subjects of teaching. In other words, the concept of teaching plays an important role in guiding educators to carry out their duties as educators in serving the learning needs of their students. Lesson plan is also intended as a first step before the learning process takes place. So that the concept of Arabic teaching can be interpreted as the process of composing the subject matter, the use of instructional media, the use of learning methods and assessment in a time allocation that will be implemented at a certain time to achieve the competence of mastery Arabic language that has been determined beforeKeywords: concept, teaching, arabic language  AbstrakDalam setiap proses pembelajaran yang berlangsung selalu ada konsep atau perencanaan yang telah direncanakan oleh guru, karena konsep merupakan pedoman untuk melangkah ke depan untuk mendapatkan hasil yang sesuai dengan apa yang diharapkan. Dalam pengajaran bahasa Arab konsep dasar adalah  gagasan/perencanaan awal yang sudah disiapkan untuk mengajar bahasa arab sesuai dengan aktivitas atau proses pengajaran antara pendidik dan peserta didik. Kunci pokok pengajaran bahasa arab itu ada pada seorang guru. Tetapi ini bukan berarti dalam dalam proses pengajaran hanya guru yang aktif, sedangkan peserta didik pasif. Pengajaran menuntut keaktifan kedua pihak yang sama-sama menjadi subyek pengajaran. Dengan kata lain bahwa konsep pengajaran memainkan peran penting dalam memandu pendidik untuk melaksanakan tugas sebagai pendidik dalam melayani kebutuhan belajar anak didiknya. Perencanaan pengajaran juga dimaksudkan sebagai langkah awal sebelum proses pembelajaran berlangsung. Sehingga konsep pengajaran bahasa Arab dapat diartikan sebagai proses penyusunan materi pelajaran, penggunaan media pengajaran, penggunaan metode pembelajaran dan penilaian dalam suatu alokasi waktu yang akan dilaksanakan pada masa tertentu untuk mencapai kompetensi penguasaan bahasa Arab yang telah ditentukan sebelumnya.Kata kunci: Konsep, Pengajaran, bahasa Arab